IMPLEMENTASI MODEL DISCOVERY LEARNING DENGAN PENDEKATAN DEEP LEARNING PADA MAPEL IPS - Dwi Aryani, Wulan (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2025)
This study aims to: (1) examine the implementation of the discovery learning model with a deep learning approach in social studies; (2) identify the supporting factors; and (3) reveal the inhibiting factors in its implementation in class IXG of SMPN 1 Kandeman. The data collection techniques consisted of observation, interviews, and documentation, while the data were analyzed using a descriptive qualitative method. The findings show that: (1) the implementation of discovery learning with a deep learning approach was carried out through three stages: planning, implementation, and evaluation by integrating deep learning experiences, learning frameworks, and the use of digital technology. This process successfully created an active, engaging, and interactive learning atmosphere while enhancing students dependence, conceptual understanding, critical thinking, creativity, communication, and collaboration; (2) the supporting factors included teacher creativity, digital technology integration, a conducive learning environment, and the relevance of the material to real life contexts; and (3) the inhibiting factors consisted of limited digital infrastructure, differences in students’ abilities, and time constraints. In conclusion, the implementation of discovery learning with a deep learning approach proved effective in fostering meaningful conceptual understanding and strengthening graduate profile dimensions, particularly creativity, collaboration, and communication.